Proteinaceous α-amylase inhibitors of Setaria italica Linn (Co-6) and its effect on α-amylase from human saliva and Bacillus sp - Vinoth Kumar Thirumalairaj, Pamala Auxlin Anitha, Geetharamani Durairaj, Sudha G Menon, Lakshmanasenthil Shanmugaasokan (Journal of Applied Pharmaceutical Science, 2014)
The specific α-amylase inhibitory activity of Setaria italica Linn (Co-6) was determined by using heat-treated and ammonium sulphate precipitated fractions of α-amylase isolated from Bacillus sp. The α-amylase inhibitor from S. italica Linn (Co-6) was precipitated with 1.0 M fraction of ammonium sulphate and used for further purification and characterization. To overcome the endogenous α-amylase activity, the extract was subjected to the heat treatment at 60 ºC. Complete loss of α-amylase inhibitory activity of the millet extract was evidenced above 85 °C. The results of this study suggest that, the use of S. italica Linn (Co-6) flour exhibits significant α-amylase inhibitory activity, in a dose dependent manner for Non- Insulin Dependent Diabetes Mellitus (NIDDM).
Keywords: Enzyme, inhibitor,diabetes mellitus, NIDDM.